2018
DOI: 10.1007/s12070-018-1249-z
|View full text |Cite
|
Sign up to set email alerts
|

Maximising Graft Take-Up in Type1 Tympanoplasty Using Peripheral Cartilage Ring and Perichondrium

Abstract: The aim of this study is to evaluate the results of closure of big central and subtotal perforation by Tympanoplasty using underlay technique with Composite graft of tragal perichondrium supported by a ring of cartilage peripherally. Our hypothesis was that the cartilage support offers an extremely reliable method for reconstruction of the tympanic membrane in cases of advanced middle ear pathology and Eustachian tube dysfunction and also revision cases. Prospective study of patients undergoing tympanoplasty i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This composite grafting system gave a 93% success rate with tympanic membrane reconstruction and nearly 80% air-bone gap closure rate. 15 Gozeler et al in a prospective study spanning over three years, compared fascia grafting with composite fascia-cartilage graft in Type-I tympanoplasty of 113 patients. Tympanic membrane closure rate and air bone-bone gap closure rates were statistically better in composite fascia cartilage grafting compared to fascia alone grafts.…”
Section: Discussionmentioning
confidence: 99%
“…This composite grafting system gave a 93% success rate with tympanic membrane reconstruction and nearly 80% air-bone gap closure rate. 15 Gozeler et al in a prospective study spanning over three years, compared fascia grafting with composite fascia-cartilage graft in Type-I tympanoplasty of 113 patients. Tympanic membrane closure rate and air bone-bone gap closure rates were statistically better in composite fascia cartilage grafting compared to fascia alone grafts.…”
Section: Discussionmentioning
confidence: 99%
“…In another study [10], 95% success rate is reported with boomerang-shaped chondroperichondrial graft. Another study reported 93% success rate of graft takeup based on composite graft comprising perichondrium and peripheral ring of tragal cartilage [11]. New technique is introduced called Cartilage plug or butterfly cartilage tympanoplasty which is considered to be pioneered by Evaey in 1998.…”
Section: Discussionmentioning
confidence: 99%